Literature Review: 21st Century Skill-Based Learning Model in Junior High School Science Learning - Cahayu, Sri Anika; Asyhar, Rayandra; Hariyadi, Bambang; Hasibuan, Muhammad Haris Effendi (IJER (Indonesian Journal of Educational Research), 2024)
21st century skills are technology-based learning, characterized by the development of information, computing, automation, and communication. This certainly has an impact on the education applied to how the learning model can meet all the challenges and demands of 21st century skills. The purpose of this study is to review learning models based on Abab 21 skills and evaluate them through an analysis of 4C skill indicators. The research method used in this study was a qualitative descriptive method. The data collection technique used in this study was library research or online literature review from sources such as Google Schoolar, Research Gate, SINTA, and DOAJ. The technique used in collecting articles uses a Publish or Perish (PoP) application with the PRISMA technique, which has stages of identification, screening, eligibility, and inclusion. The results of the study show that 21st century learning models in science learning are flipped classroom, project-based learning (PjBL), problem-based learning (PBL), blended learning model (MBL), and incuiry and discovery learning. The indicators of 4C skills are critical thinking (FRISCO), creative thinking (fluency, flexibility, originality, and elaboration), communication, and collaboration (respect, willingness, and compromise). The application of these learning models must be carried out optimally in accordance with the indicators used to develop 21st century skills in students.